Satellite radar interferometry (InSAR) - Lee, Felicia Pei Qi (2017)
Interferometric synthetic aperture radar (InSAR) makes use of high-resolution SAR images to generate high quality terrain elevation maps using interferometric processing methods. It is able to provide a continuous imagery regardless of the weather conditions. It has also been playing a crucial role in the enhancement of Earth observation sciences as the development of InSAR technology has been constantly improving and growing in research fields. In this report, the three main steps in interferometric processing, as well as digital elevation models (DEMs) are being discussed.